1996
DOI: 10.1002/art.1790090106
|View full text |Cite
|
Sign up to set email alerts
|

The social network characteristics of fibromyalgia patients compared with healthy controls

Abstract: Objective. To assess structural social network characteristics and perceived loneliness in fibromyalgia syndrome (FMS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 17 publications
3
10
0
1
Order By: Relevance
“…This was somewhat surprising in light of existing literature in which interpersonal strains often were reported by persons with FMS. Our results are more in accord with those of a previous study by Bolwijn, van Santen-Hoeufft, Baars, Kaplan, and van der Linden (1996) who reported fairly robust social network ties in persons with FMS.…”
Section: Discussionsupporting
confidence: 96%
“…This was somewhat surprising in light of existing literature in which interpersonal strains often were reported by persons with FMS. Our results are more in accord with those of a previous study by Bolwijn, van Santen-Hoeufft, Baars, Kaplan, and van der Linden (1996) who reported fairly robust social network ties in persons with FMS.…”
Section: Discussionsupporting
confidence: 96%
“…For example, whereas patients in cluster 1 presented with high pain, physical involvement, mental impairment and low social support, patients in cluster 4 had low pain, normal physical and mental function and high social support. Bolwijn et al (1996) reported that the social networks of patients with FM were more restricted, closed and could hardly fulfil psychosocial needs. Consistently, patients in cluster 2 exhibited moderate social support and moderate pain levels, physical impairment and mental impairment.…”
Section: Discussionmentioning
confidence: 99%
“…It is also evident that patients with FM experience low levels of social support. Bolwijn et al (1996) reported that the social networks of patients with FM were more restricted, closed and could hardly fulfil psychosocial needs. In addition, Montoya et al (2004) showed that when social support was provided, patients with FM had less pain and thermal pain sensitivity and displayed decreased brain activity upon tactile stimulation of a tender point, suggesting that social support also influences central nervous system involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Participants in our study had a mean network size of 5.7 of a possible 12 people that could be listed. Another study that examined the size of the social support networks of people with FMS reported a mean social network size of 32.6, which included an average of 4.5 intimate friends, 5 acquaintances, 1.5 health care providers, and 23.2 family members Bolwijn, Santen-Hoeufft, Baars, Kaplan, & Linden, 1996!. The number of intimate members of the individual's network reported in the Bolwijn et al study is similar to the mean network size reported in our study.…”
Section: Social Supportmentioning
confidence: 98%